1992
DOI: 10.1523/jneurosci.12-12-04867.1992
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis within neuronal growth cones

Abstract: This study investigates the capacity of neuronal growth cones to synthesize protein locally and independently of their cell body. Isolated growth cones were prepared from cultures of neurons from the snail Helisoma by transecting neurites proximal to the growth cone. The capacity for protein synthesis was tested by radiolabeling cultures with 3H-leucine and analyzing the resultant autoradiograms. Isolated growth cones displayed incorporation of 3H-leucine that was inhibited by treatment with the protein synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
2
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 29 publications
2
48
2
1
Order By: Relevance
“…While neurites at this stage have not yet differentiated into axons or dendrites, there is little doubt that young growth cones have the capacity to synthesize protein. Indeed, the detection of polysomes by electron microscopy (16) and the incorporation of radiolabeled amino acids into protein into isolated growth cones (15) demonstrate that translation does occur in this structure. Moreover, axon turning in vitro in response to exogenous cures also requires protein synthesis, although it is not known if this takes place in the growth cone, the axon shaft, or both (69).…”
Section: Discussionmentioning
confidence: 99%
“…While neurites at this stage have not yet differentiated into axons or dendrites, there is little doubt that young growth cones have the capacity to synthesize protein. Indeed, the detection of polysomes by electron microscopy (16) and the incorporation of radiolabeled amino acids into protein into isolated growth cones (15) demonstrate that translation does occur in this structure. Moreover, axon turning in vitro in response to exogenous cures also requires protein synthesis, although it is not known if this takes place in the growth cone, the axon shaft, or both (69).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of cytoplasmic protein synthesis in mammalian nerve endings is also indirectly suggested by the existence of a translation system in growth cones (66,190). In a number of experiments, this system has been shown to play an essential role in axon guidance during development (37,42,204,231,332,333).…”
Section: B Nerve Terminalsmentioning
confidence: 99%
“…Localized protein synthesis in dendrites is a well-accepted mechanism that that can be regulated by neurotransmitters and trophic factors (Steward, 2002). Evidence for protein synthesis in axons was initially provided from studies in invertebrates (Capano et al, 1987;Giuditta et al, 1991;Davis et al, 1992;Chun et al, 1996;van Minnen et al, 1997). Subsequent work showed that developing vertebrate axons contain mRNAs and actively synthesize proteins (Olink-Coux and Hollenbeck, 1996;Bassell et al, 1998;Eng et al, 1999;Zhang et al, 1999;Aronov et al, 2001;Campbell and Holt, 2001; Lee and Hollenbeck, 2003).…”
Section: Introductionmentioning
confidence: 99%